Physical fitness improvements of 8-week light vs. heavy tyre flip training in young adults - Wong, Del; Weldon, Anthony; Ngo, Jake (Biology of Sport, 2020)
This study compared the effects of eight-week tyre flipping training intervention using light and heavy tyres on physical fitness performance. Twenty-nine young physically active males were divided into light (n = 15) and heavy (n = 14) tyre flipping groups evenly according to body weight and height. Body-to-tyre weight ratios were 0.61 ± 0.06 for the light tyre (LTTG) and 1.51 ± 0.16 for the heavy tyre training (HTTG) groups. Fitness parameters were measured before and after the intervention. One-way ANCOVA analysis indicated no significant between-group differences when pre-test values were controlled. Both groups demonstrated within-group improvements in 6RM bench press (ES: 0.98 in LTTG and 1.10 in HTTG), intermittent endurance (ES: 0.45 in LTTG and 0.66 in HTTG), five horizontal jumps (ES: 0.35 in LTTG and 0.26 in HTTG), and agility (ES: 0.34 in LTTG and 0.41 in HTTG). Both groups improved tyre flipping efficiency, through decreasing average set duration and work-rest ratios in the first six training sessions, and reached a plateau starting from the 7th training session. This study provides the first empirical evidence for coaches to justify usage of tyre flip training and the timing to progressive overload for a population with limited weight training and no tyre flip training experience.